2014
DOI: 10.1051/odfen/2014006
|View full text |Cite
|
Sign up to set email alerts
|

Healing processes following tooth extraction in orthodontic cases

Abstract: This article reviews the normal and pathological healing processes that take place after tooth extraction in orthodontic cases, and their associated complications within the mucosa or alveolar socket, such as gingival clefts or bone defects. The general and local factors that are involved in such deficient healing cases are detailed, in parallel to surgical procedure to enhance ridge preservation or to 'regenerate' tissues. The relationships between the orthodontist and periodontist are underlined, because bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 57 publications
(58 reference statements)
0
21
0
Order By: Relevance
“…The rapid healing potential of the extraction socket has generated interest, because it greatly influences subsequent dental treatment. A human study demonstrated that mineralization begins at the end of the first week, and that most of the granulation tissue has been replaced with a provisional matrix and immature bone by the sixth to eighth week of post-extraction healing [ 30 ]. However, because rat extraction sockets are considered to be a non-critical size defect, the socket will be gradually filled by newly-formed bone [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rapid healing potential of the extraction socket has generated interest, because it greatly influences subsequent dental treatment. A human study demonstrated that mineralization begins at the end of the first week, and that most of the granulation tissue has been replaced with a provisional matrix and immature bone by the sixth to eighth week of post-extraction healing [ 30 ]. However, because rat extraction sockets are considered to be a non-critical size defect, the socket will be gradually filled by newly-formed bone [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages perform their function as phagocytes for three days after the occurrence of lesions and will continue to do so as a means of promoting the formation of granulated tissue and the process of angiogenesis with the support of fibroblasts, keratinocytes, and endothelial cells until the seventh day. Furthermore, the formation of connective tissue and the process of angiogenesis will be followed by a phase of bone remodeling when osteoclasts die through a process of apoptosis and osteoblasts promote the formation of new cells (Ahsania, 2019;Cohen & Cohen-Lévy, 2014;Wang et al, 2017).…”
Section: Journal Ofmentioning
confidence: 99%
“…This research was conducted on the third day during which the macrophages entered the lesion area to phagocytosis (Cohen & Cohen-Lévy, 2014) and on the seventh day when the macrophages supported the proliferation phase of the wound healing process by producing several interleukins and growth factors (Wang et al, 2017). In this study, propolis extract was used because it produces an immunostimulatory effect that can increase the number of macrophages which it is anticipated will accelerate the wound healing process due to tooth extraction (Herawati et al, 2017).…”
Section: Journal Ofmentioning
confidence: 99%
“…In contrast, "normal healing" was defined as extraction sockets without symptoms, including pain, and with sufficient colonization of granulation tissue 1 week after dental extraction. 14 The AUC describes how well the predictive model discriminates cases with from without delayed socket healing. The AUC ranges from 0.5 to 1.0, where 0.5 is used as the reference and 1.0 indicates perfect prediction.…”
Section: Outcome Variablementioning
confidence: 99%